Pelatihan Penelitian Tindakan Kelas (PTK) Untuk Guru di MGMP Pendidikan Kewarganegaraan Kota Jayapura - Ode Jamal; Benyamina Lorina Marbo (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Classroom Action Research (CAR) training for teachers at the MGMP Citizenship Education in Jayapura City aims to improve teachers' professional competence in conducting research oriented towards improving the learning process. This study uses a qualitative method with a descriptive approach. The results of the training show an increase in teachers' understanding of the concept of CAR and its application in learning. This finding makes a significant contribution to the development of education in Jayapura City.